Analisis Program Dakwah pada Radio-Radio Siaran Swasta Niaga di Kalimantan Selatan - Surianor Surianor (Alhadharah: Jurnal Ilmu Dakwah, 2016)
South Kalimantan has many private radio stations, and even the number reached 16 pieces. Most private radio stations, there were also broadcast events nuanced propaganda or propagation of Islam, but the percentage is very small. Her shows are more regular lectures by replaying tapes of local scholars lecture, recitation of the Qur'an regularly, azan Maghrib and playback song as Islamic. Less encountered events propaganda treated seriously by the team work through the production process. Even some of the radio broadcast events only Christianity and not explicitly include event propagation of Islam. Turns out all that much due to the status of radios, such as the private commercial radio, and its owners are generally among the Chinese non-Muslims, and there are very few Muslim businessmen who want to plunge into the radio business.Keywords: da’wa, private commercial radio, broadcastingKalimantan Selatan memiliki banyak radio swasta, bahkan jumlahnya mencapai 16 buah. Kebanyakan radio-radio swasta tersebut ada juga menyiarkan acara-acara dakwah atau bernuansa dakwah Islam, namun persentasinya sangat kecil. Acara-acaranya lebih bersifat ceramah rutin dengan memutar ulang kaset-kaset rekaman ceramah ulama lokal, pengajian Alquran rutin, adzan Maghrib serta pemutaran lagu-lagu bernuansa islami. Kurang ditemui acara-acara dakwah yang diolah secara sungguh-sungguh oleh tim kerja melalui proses produksi. Bahkan beberapa radio hanya menyiarkan acara agama Kristen dan tidak secara eksplisit mencantumkan acara dakwah Islam. Ternyata semua itu banyak disebabkan oleh status radio-radio tersebut sebagai radio swasta niaga, dan pemiliknya yang umumnya kalangan Tionghoa nonmuslim, dan sedikit sekali ada pengusaha muslim yang mau terjun ke dalam bisnis radio.Kata kunci: dakwah, radio swasta niaga, siaran.